2011
DOI: 10.1016/j.ajpath.2011.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Helper T-Cell Cytokines Induce Morphologic and Molecular Characteristics of Atopic Dermatitis in Human Skin Equivalent

Abstract: Both the immune system and the epidermis likely have an important role in the pathogenesis of atopic dermatitis (AD). The objective of the present study was to develop a human skin equivalent model exhibiting morphologic and molecular characteristics of AD in a controlled manner. Skin equivalents generated from normal adult human keratinocytes were stimulated with type 2 T-helper cell (Th2) cytokines IL-4 and IL-13, and morphologic features and gene expression of the epidermis were studied. Th2 cytokines induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 46 publications
4
71
1
4
Order By: Relevance
“…1a). Conversely, RHE treated with IL-4, IL-13 and IL-25 for 48 hours displayed intercellular space widening similar to spongiosis (already reported for IL-4 and IL-13 [4][5][6] ) and hypogranulosis, two histological hallmarks of lesional AD skin (Fig. S2).…”
Section: Resultsmentioning
confidence: 90%
“…1a). Conversely, RHE treated with IL-4, IL-13 and IL-25 for 48 hours displayed intercellular space widening similar to spongiosis (already reported for IL-4 and IL-13 [4][5][6] ) and hypogranulosis, two histological hallmarks of lesional AD skin (Fig. S2).…”
Section: Resultsmentioning
confidence: 90%
“…Th2 cytokines like IL-4 and IL-13 induce spongiosis and apoptosis in skin equivalents, probably via STAT6 signaling (18). These cytokines were also shown to downregulate involucrin and loricrin expression via STAT6 (4).…”
Section: Figurementioning
confidence: 99%
“…Our results reveal a key role of the AHR signaling pathway in breaching the vicious The immunopathogenesis of AD has been studied directly on patients or in animal models based on allergic immune responses (29)(30)(31). We have recently developed in vitro organotypic models for psoriasis and AD (18,19), and have shown that the application of genetic techniques in these models could be used to study epidermal aspects of diseases (32). Others showed that FLG knockdown in human skin equivalents could mimic AD skin by impaired epidermal differentiation and barrier dysfunction (33,34).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…We have previously described the use of in vitro human skin equivalents to study skin biology and inflammation [20,21,[24][25][26][27] . We here took a transgenic approach to selectively overexpress hBD2 or hBD3, using lentiviral gene delivery in primary keratinocytes as we have described previously [25] .…”
Section: Effect Of Lentiviral Delivery Of Hbd2 and Hbd3 On 3-dimensiomentioning
confidence: 99%